Multi-Representation Discourse Model and Math Problem Solving Skills of High School Students - Widhy Adnyana, Putu Gede; Suarsana, I Made; Putu Suharta, I Gusti (Journal of Learning Improvement and Lesson Study, 2021)
This research is a pseudo-experimental study that aims to determine the influence of multi-representation discourse learning model on the mathematical problem solving skills of grade X students of SMA Negeri 3 Singaraja. The design of this research is post-test only control group design. The sampling of the research was conducted by cluster random sampling technique. Sampling is done by drawing against 3 classes. In this study, class X MIPA 1 and class X MIPA 2 were selected. The draw was re-drawn to determine the experimental class and control class, the result of the drawing was selected class X MIPA 2 as the experimental class and class X MIPA 1 as the control class. Data on solving students' math problems were collected through essay tests and analyzed using one-tail t-tests at a rate of 5% significance, the results of which showed that thitung = 1,79 and ttabel = 1,67. The results showed that with the application of multi-representation discourse learning model is better than the math solving skills of students who are taught with conventional learning.